New Monoclonal Antibodies to Defined Cell Surface Proteins on Human Pluripotent Stem Cells. (19th January 2017) - O'Brien, Carmel M.; Chy, Hun S.; Zhou, Qi; Blumenfeld, Shiri; Lambshead, Jack W.; Liu, Xiaodong; Kie, Joshua; Capaldo, Bianca D.; Chung, Tung‐Liang; Adams, Timothy E.; Phan, Tram; Bentley, John D.; et al.
Abstract: The study and application of human pluripotent stem cells (hPSCs) will be enhanced by the availability of well‐characterized monoclonal antibodies (mAbs) detecting cell‐surface epitopes. Here, we report generation of seven new mAbs that detect cell surface proteins present on live and fixed human ES cells (hESCs) and human iPS cells (hiPSCs), confirming our previous prediction that these proteins were present on the cell surface of hPSCs. The mAbs all show a high correlation with POU5F1 (OCT4) expression and other hPSC surface markers (TRA‐160 and SSEA‐4) in hPSC cultures and detect rare OCT4 positive cells in differentiated cell cultures. These mAbs are immunoreactive to cell surface protein epitopes on both primed and naive state hPSCs, providing useful research tools to investigate the cellular mechanisms underlying human pluripotency and states of cellular reprogramming. In addition, we report that subsets of the seven new mAbs are also immunoreactive to human bone marrow‐derived mesenchymal stem cells (MSCs), normal human breast subsets and both normal and tumorigenic colorectal cell populations. The mAbs reported here should accelerate the investigation of the nature of pluripotency, and enable development of robust cell separation and tracing technologies to enrich or deplete for hPSCs and other human stem and somatic cell types. Stem Cells 2017;35:626–640 Graphical Abstract: We describe the generation of novel monoclonal antibodies (mAbs) for the detection and viable characterization of human pluripotent cell (hPSC) cultures and their derivative cells. To select mAb targets we used previously published transcriptional and bioinformatic data that predicts cell surface proteins correlating with the CD9/GCTM‐2 gradient identified for hPSCs cultured in multiple conditions. A large number of novel hybridomas were produced that detected cell surface proteins for known gene targets on live hPSC by flow cytometry. Here, we show detailed immunostaining and flow cytometric analyses of hPSC cultures using a panel of seven new mAbs detecting epitopes corresponding to GPR64, CDCP1, hF11R, DSG2, CDH3, NLGN4X, and PCDH1. We have analyzed the immunoreactivity of these epitopes on hPSCs cultured in a lineage primed state, during early differentiation and in three culture conditions reported to support a naive state of pluripotency. We further examined the detection of these proteins in somatic cell types relevant to the study of breast and colorectal cancers. These mAbs provide a new resource for application in the study of human pluripotency, cell reprogramming and oncogenesis.